Expression of ribosome‐binding protein 1 correlates with shorter survival in Her‐2 positive breast cancer. Issue 6 (27th April 2015) - Liang, Xiaoshuan; Sun, Shanshan; Zhang, Xianyu; Wu, Hao; Tao, Weiyang; Liu, Tong; Wei, Wei; Geng, Jingshu; Pang, Da
<x xml:space="preserve">Abstract</x> The aim of this study is to investigate the expression of ribosome‐binding protein 1 (RRBP1) in invasive breast cancer and to analyze its relationship to clinical features and prognosis. RRBP1 expression was studied using real‐time quantitative PCR and western blotting using pair‐matched breast samples and immunohistochemical staining using a tissue microarray. Then the correlation between RRBP1 expression and clinicopathologic features was analyzed. RRBP1 mRNA and protein expression were significantly increased in breast cancer tissues compared with normal tissues. The protein level of RRBP1 is proved to be positively related to histological grade (P = 0.02), molecular subtype (P = 0.048) and status of Her‐2 (P = 0.026) and P53 (P = 0.015). We performed a grade‐stratified analysis of all patients according to the level of RRBP1 expression and found that RRBP1 overexpression highly affected overall survival in patients with early‐stage (I and II) tumors (P = 0.042). Furthermore, Her‐2 positive patients with negative RRBP1 expression had longer overall survival rates than those with positive RRBP1 expression (P = 0.031). Using multivariate analysis, it was determined that lymph node metastasis (LNM, P = 0.002) and RRBP1 expression (P = 0.005) were independent prognosis factors for overall survival. RRBP1 is a valuable prognostic factor in Her‐2‐positive breast cancer patients, indicating that RRBP1 is a potentially important target for the prediction of prognosis.